2005
DOI: 10.2460/ajvr.2005.66.2149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surveillance and sample collection methods to document freedom from infectious bovine rhinotracheitis in cattle populations

Abstract: Geographically targeted sample collection during the high-risk season (winter) was predicted to increase the probability of rapid detection of IBR infection in cattle. This approach can be used for assessing other surveillance systems to determine the best strategies for detection of infected herds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The effect of season has modified surveillance strategies for infectious diseases. In Denmark, for example, it has been recommended that sampling for infectious bovine rhinotracheitis (IBR) occurs primarily during the winter months of the year (Chriel et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of season has modified surveillance strategies for infectious diseases. In Denmark, for example, it has been recommended that sampling for infectious bovine rhinotracheitis (IBR) occurs primarily during the winter months of the year (Chriel et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the comparison of the sensitivity of the currently targeted surveillance system for classical swine fever (CSF) in Denmark with that of a simulated non‐targeted system identified that the current system was twice as sensitive compared with the simulated, non‐targeted system (Martin et al., 2007a). In another Danish example, the sensitivity of the current surveillance programme for infectious bovine rhinotracheitis (IBR) was compared with three other surveillance scenarios targeting specific geographical areas and risk periods (Chriel et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Stochastic simulation models are commonly used to evaluate the sensitivity and specificity of surveillance systems (4,9,25) and evaluate the effects of different sample collection methods (31), sample sizes (7), surveillance or eradication strategies (11,36,41,42,47,49,56) and serological tests (34). The effect of different sampling collection conditions when testing for infectious bovine rhinotracheitis was evaluated with a simulation model (8,40). A simulation model was also used to determine that the sample size for an abattoir-based survey was too small to estimate a true prevalence of scrapie of 1% with an accuracy of ±0.5% (50).…”
Section: Evaluating Surveillance Systemsmentioning
confidence: 99%
“…Epidemiological models have been used to estimate the probability that disease is absent in a population or herd (7,8,9,13,23,27,28,29,32,33,35,40,51). It is impossible to prove that a population is free from disease or infection without testing each and every animal in that population.…”
Section: Document the Absence Of Disease Or Infectionmentioning
confidence: 99%